How to build a mobile website - Turner, Jamie, 1961- (FTPress, 2012)
You need to create great sites that are clean and simple, load quickly, and are optimized to serve the needs of mobile users; and understand how customers want to engage with your brand via mobile. By 2013, the #1 way people will access the Internet will be via mobile device. Currently, mobile coupons are redeemed 10x more frequently than traditional coupons. Your company needs a website that delivers an outstanding mobile experience. If you build websites for a living, you need to know how to create great mobile sites. Jamie Turner's How to Build a Mobile Website is the place to start. Turner begins by reviewing the current mobile landscape and helping you get into your customers' minds to understand how they want to interact with your brand online. You'll compare three leading approaches to "mobilizing" websites and discover how to avoid pitfalls that lead directly to a poor experience and lost customers. Next, Turner offers a high-level overview of the mechanics of mobile site development, construction, and testing, addressing issues ranging from consistent branding to performance and usability. He also shares tips ranging from linking back to your main site to building "thumb-friendly" pages. Throughout, the focus is on building sites that are clean and simple, load quickly, and are fully optimized to serve the needs of mobile users: today's best customers .